10.4k views
2 votes
Please Help. Lateena solved the equation below. Is her solution correct? Explain why or why not?

I've attached the picture for the problem.

Please Help. Lateena solved the equation below. Is her solution correct? Explain why-example-1
User Oshliaer
by
5.8k points

1 Answer

4 votes

Answer:

Not correct

Explanation:

Given:

x² - 6x - 7 = 0

The following equation can be solved correctly by factoring Thus,

x² - x + 7x - 7 = 0

x(x - 1) +7(x - 1) = 0

(x - 1)(x + 7) = 0

(x - 1) = 0

x - 1 = 0

x - 1 + 1 = 0 + 1

x = 1

Or

(x + 7) = 0

x + 7 = 0

x + 7 - 7 = 0 - 7

x = -7

Therefore, the solution would be x = 1 or x = -7

Lateena solution is therefore NOT CORRECT because she used a wrong method.

User Raghul
by
5.3k points